+0  
 
+16
761
0
avatar+19597 

I can't find the original question, here is the answer for

\(|z-1|+z=3-i \)

 

 

1. Formula:

\(\begin{array}{|rcll|} \hline z &=& a+bi \\ |z| &=& \sqrt{a^2+b^2} \\ \hline \end{array} \)

 

2. |z-1|:

\(\begin{array}{|rcll|} \hline |z-1| = |a+bi-1| &=& |(a-1)+bi| \\ &=& \sqrt{(a-1)^2+b^2} \\ &=& \sqrt{a^2-2a+1+b^2} \\ \hline \end{array} \)

 

\(\begin{array}{|rcll|} \hline |z-1|+z &=& 3-i \\\\ \overbrace{\underbrace{\sqrt{a^2-2a+1+b^2} +a}_{=3}}^{Re(z)}+\overbrace{\underbrace{b}_{=-1}\cdot i}^{Im(z)} &=& 3-1\cdot i \\\\ \Rightarrow \mathbf{b} & \mathbf{=} & \mathbf{-1} \\\\ \Rightarrow \sqrt{a^2-2a+1+b^2} +a &=&3 \quad &| \quad b=-1\\ \sqrt{a^2-2a+1+(-1)^2} +a &=& 3 \\ \sqrt{a^2-2a+1+1} +a &=& 3 \\ \sqrt{a^2-2a+2} +a &=& 3 \quad &| \quad - a\\ \sqrt{a^2-2a+2} &=& 3-a \quad &| \quad \text{square both sides} \\ a^2-2a+2 &=& (3-a)^2 \\ \not{a^2}-2a+2 &=& 9-6a+\not{a^2} \\ -2a+2 &=& 9-6a \quad &| \quad +6 a\\ 6a-2a+2 &=& 9 \quad &| \quad -2 \\ 4a &=& 9-2 \\ 4a &=& 7 \quad &| \quad :4\\ \mathbf{a} & \mathbf{=} & \mathbf{\frac74} \\ \hline \end{array} \)

 

3. z:

\(\begin{array}{|rcll|} \hline z &=& a+bi \\ z &=& \frac74-1\cdot i \\ \mathbf{z} & \mathbf{=} & \mathbf{\frac74- i} \\ \hline \end{array}\)

 

laugh

 
heureka  Jan 18, 2017

14 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.